Low Abundance Fusobacterium Nucleatum Supports Early Pregnancy Development – An In Vitro Study - Heusler, Martha; Einenkel, Rebekka; Ehrhardt, Jens; Muzzio, Damián Oscar; Zygmunt, Marek (Frontiers in Immunology, 2021)
Pregnancy success depends greatly on a balanced immune homeostasis. The detection of bacterial components in the upper reproductive tract in non-pregnant and pregnant women raised questions on its possible beneficial role in reproductive health. The local conditions that allow the presence of bacteria to harmonize with the establishment of pregnancy are still unknown. Among the described bacterial species in endometrial and placental samples, Fusobacterium nucleatum was found. It has been observed that F. nucleatum can induce tumorigenesis in colon carcinoma, a process that shares several features with embryo implantation. We propose that low concentrations of F. nucleatum may improve trophoblast function without exerting destructive responses. Inactivated F. nucleatum and E. coli were incubated with the trophoblastic cell lines HTR8/SVneo, BeWo, and JEG-3. Viability, proliferation, migratory capacity, invasiveness and the secretion of chemokines, other cytokines and matrix metalloproteinases were assessed. The presence of F. nucleatum significantly induced HTR8/SVneo invasion, accompanied by the secretion of soluble mediators (CXCL1, IL-6 and IL-8) and metalloproteinases (MMP-2 and MMP-9). However, as concentrations of F. nucleatum increased, these did not improve invasiveness, hindered migration, reduced cell viability and induced alterations in the cell cycle. Part of the F. nucleatum effects on cytokine release were reverted with the addition of a TLR4 blocking antibody. Other effects correlated with the level of expression of E-cadherin on the different cell lines tested. Low amounts of F. nucleatum promote invasion of HTR8/SVneo cells and induce the secretion of important mediators for pregnancy establishment. Some effects were independent of LPS and correlated with the expression of E-cadherin on trophoblasts.